Guardians of finance : making regulators work for us - Barth, James R; Caprio, Gerard; Levine, Ross (Cambridge, MA MIT Press, 2012)
"​The recent financial crisis was an accident, a "perfect storm" fueled by an unforeseeable confluence of events that unfortunately combined to bring down the global financial systems. Or at least this is the story told and retold by a chorus of luminaries that includes Timothy Geithner, Henry Paulson, Robert Rubin, Ben Bernanke, and Alan Greenspan. In Guardians of Finance, economists James Barth, Gerard Caprio, and Ross Levine argue that the financial meltdown of 2007 to 2009 was no accident; it was negligent homicide. They show that senior regulatory officials around the world knew or should have known that their policies were destabilizing the global financial system and yet chose not to act until the crisis had fully emerged. Barth, Caprio, and Levine propose a reform to counter this systemic failure: the establishment of a "Sentinel" to provide an informed, expert, and independent assessment of financial regulation. Its sole power would be to demand information and to evaluate it from the perspective of the public--rather than that of the financial industry, the regulators, or politicians". (from Amazon page)
1 Introduction -- 2 Regulating finance is hard to do -- 3 Incentives run amok -- 4 How US regulators encouraged the financial crisis -- 5 American crisis? aint necessarily so -- 6 Been down this road many times before -- 7 More of the same:post 2007-2009 financial crisis regulation -- 8 Making the guardians of finance work for Us
Includes Bibliographical References and Index.
Keywords: Money; BANKING; MONETARY CRISIS; FINANCE; Financial economics; Financial crises; FINANCIAL INSTITUTIONS